Diffusion of Pneumocystis jirovecii in the surrounding air of patients with Pneumocystis colonization: frequency and putative risk factors. (2nd November 2016) - Fréalle, Emilie; Valade, Sandrine; Guigue, Nicolas; Hamane, Samia; Chabé, Magali; Le Gal, Solène; Damiani, Céline; Totet, Anne; Aliouat, El Moukhtar; Nevez, Gilles; Menotti, Jean
Abstract: In a prospective bicentric study, Pneumocystis jirovecii excretion and diffusion was explored in air samples collected in the rooms occupied by 17 Pneumocystis -colonized patients. P. jirovecii DNA was detected by real-time PCR in the air collected from 3 patients' rooms (17.6%), with identical genotypes in corresponding clinical and air samples. Pneumocystis DNA was detected for 2/3 patients with autoimmune disease treated with corticosteroids versus 1/6 patients with hematologic disease and 0/5 kidney transplant recipients. These data confirm the possible excretion of the fungus by Pneumocystis -colonized patients and thus bring additional arguments for the prevention of airborne transmission in hospital wards.